Disaster management takes to the skies: How new technologies are reconfiguring spatialities of power in desert locust management - Enns, Charis; Bersaglio, Brock; Karmushu, Ramson (Political geography, 2022)
This article explores how new technologies – such as drones and satellites – are incorporated into disaster management and questions the implications for power relations between disaster authorities and subjects. This is a critical area of research, as the proliferation of aerial and networked technologies has made their use in disaster management and response more common. Although concerns have been raised about the potential use of aerial and networked technologies in the surveillance and spatial discipline of populations by commercial and government actors, few have considered the implications for disaster management. In response, this article turns to geographical literature on necropower, verticality, and planetary spatialities to analyse technological innovations in responses to desert locust upsurges in Kenya. Drawing from qualitative research carried out between February 2020 and January 2021, we explain how desert locust control operations have shifted from horizontal to vertical to networked and planetary in nature through experimentation with new technologies over the past century. We argue that aerial and networked technologies have led to a volumetric shift in desert locust management and response, giving remote and increasingly automated actors who operate ‘above’ greater power over the life and death of populations ‘below’. In making this argument, we adopt a more-than-human perspective to account for how nonhuman entities and lifeforms shape and are subjected to necropolitical disaster management and responses. We conclude by reflecting on what this analytical approach has to offer the study of vertical and volumetric geographies. •New technologies are increasingly central to disaster management.•These technologies are reorienting disaster action around volumetric, planetary space.•This means new actors and authorities are calculating disaster interventions.•Emerging spatialities of disaster actions have implications for power asymmetries.•The new technologies we focus on are largely aerial, automated, and autonomous.